Glass coating natural fibres by diatomisation: A bright future for biofouling technology. (June 2016) - Zusron, Muhammad; Sanka, Immanuel; Nuhamunada, Matin; Damayanti, Yudithia; Nopitasari, Sri; Kamila, Afina Dina; Kusuma, Alfian Bani; Ningrum, Eka Fitriana Chandra; Rahmawati, Annisa Resa; Zakiyah, Nibras; Islami, Dinda Ayu; Prabaswara, Cakra Buwana; et al.
Graphical abstract: Abstract: This article concerns a biotechnological method by which natural bioglass diatoms can be attached to natural fibre surfaces. We consider the attachment energetics of diatom extracellular polymers to the main constituents of flax fibre surfaces (cellulose, hemicellulose and lignin) and find that after attachment, certain diatom frustule geometries are more or less effective in improving fibre bending and tensile resistance. We postulate mechanisms by which different bioglass diatom frustule geometries are able to reinforce natural fibres. Our research opens new channels by which means natural fibres can have their properties improved through diatomisation biofouling technologies.